Management of TMD without surgery using prolotherapy with dexamethasone, aquades, and lidocaine hcl for pain and inflammation relief: A case series - Adhe Ismunandar (Indonesia Prosthodontic Association, 2025)
Background: Temporomandibular Disorder (TMD) is a condition involving inflammation of the temporomandibular joint (TMJ) that causes pain and discomfort. Non-surgical treatments such as prolotherapy using dexamethasone, aquades, and lidocaine HCl have shown potential in managing these symptoms.Case Series: Three TMD patients received prolotherapy treatments containing dexamethasone, aquades, and lidocaine HCl. The treatment effectively reduced pain and inflammation in the patients.Results: Significant reductions in pain and inflammation were observed post-treatment, with improved joint mobility and quality of life for the patients.Conclusion: Prolotherapy with dexamethasone, aquades, and lidocaine HCl is a promising non-surgical treatment for TMD, showing significant reductions in pain and inflammation.Keywords: Temporomandibular Disorder, Prolotherapy, Dexamethasone, Lidocaine HCl, Pain Reduction, Inflammation, Non-Surgical Treatment.